2015
DOI: 10.1002/cncr.29481
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian cancer treatment: The end of empiricism?

Abstract: The diagnosis, investigation, and management of ovarian cancer are in a state of flux—balancing ever rapid advances in our understanding of its biology with 3 decades of clinical trials. Clinical trials that started with empirically driven selections have evolved in an evidence‐informed manner to gradually improve outcome. Has this improved understanding of the biology and associated calls to action led to appropriate changes in therapy? In this review, the authors discuss incorporating emerging data on biolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 90 publications
(127 reference statements)
0
28
0
Order By: Relevance
“…Therefore, it is possible that combining bevacizumab with paclitaxel plus carboplatin could decrease the platinum-resistant recurrence rate. Recurrence eventually affects 70–80% of patients with advanced epithelial ovarian cancer [2, 22], with platinum sensitivity and primary PFI being repowered as prognostic factors for recurrent epithelial ovarian cancer [22, 23]. Furthermore, it is currently reported that the concept of “platinum sensitivity” based on the platinum-free interval may also be applicable to patients who have been previously treated with bevacizumab plus platinum-based chemotherapy [24].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is possible that combining bevacizumab with paclitaxel plus carboplatin could decrease the platinum-resistant recurrence rate. Recurrence eventually affects 70–80% of patients with advanced epithelial ovarian cancer [2, 22], with platinum sensitivity and primary PFI being repowered as prognostic factors for recurrent epithelial ovarian cancer [22, 23]. Furthermore, it is currently reported that the concept of “platinum sensitivity” based on the platinum-free interval may also be applicable to patients who have been previously treated with bevacizumab plus platinum-based chemotherapy [24].…”
Section: Discussionmentioning
confidence: 99%
“…It is imperative to consider disease biology when evaluating choice of therapy as well as the sequence of surgery/systemic therapy. Surgery clearly has a major impact on reducing tumor burden, and this is important when systemic therapy is less effective, as in low‐grade serous, clear cell, and mucinous carcinoma subtypes . Evaluating and incorporating biologic predictive biomarkers for R0 debulking remains an active area of development.…”
Section: Treatment Of Ovarian Cancer—surgery Systemic Therapy and Rmentioning
confidence: 99%
“…None of these agents stand out as superior over others in terms of safety or efficacy. Furthermore, the clinical experience in advanced and relapsed EOC has shown that addition of a third cytotoxic compound to existing chemotherapeutic regimens results in increased toxicity without improving disease control [19][20][21]. Maintenance therapy with conventional cytotoxic agents has not demonstrated any meaningful OS benefit, yet cumulative toxicity associated with long-term chemotherapy has emerged as a major clinical concern [22].…”
Section: Ovarian Cancer Landscapementioning
confidence: 99%